2018
DOI: 10.1108/itp-10-2017-0322
|View full text |Cite
|
Sign up to set email alerts
|

Examining employee security violations: moral disengagement and its environmental influences

Abstract: Purpose Employee security behaviors are the cornerstone for achieving holistic organizational information security. Recent studies in the information systems (IS) security literature have used neutralization and moral disengagement (MD) perspectives to examine employee rationalizations of noncompliant security behaviors. Extending this prior work, the purpose of this paper is to identify mechanisms of security education, training, and awareness (SETA) programs and deterrence as well as employees’ organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…36 , 37 In our study, SETA programs refer to hospital staff’s perceived level of proficiency on common knowledge of information security environment, along with required information security skills provided by hospitals. 49 Prior evidence confirms that a SETA program can improve employees’ self-efficacy on security, 50 motivate employees to comply with security policy, 51 and increase employees’ perceptions concerning punishment severity and punishment certainty. 17 Therefore, hospital staff who attend these SETA programs are expected to possess a deeper knowledge about punishments of non-compliance to the ISP in addition to regular security policies and procedures.…”
Section: Theoretical Foundation Research Model and Hypothesesmentioning
confidence: 93%
See 1 more Smart Citation
“…36 , 37 In our study, SETA programs refer to hospital staff’s perceived level of proficiency on common knowledge of information security environment, along with required information security skills provided by hospitals. 49 Prior evidence confirms that a SETA program can improve employees’ self-efficacy on security, 50 motivate employees to comply with security policy, 51 and increase employees’ perceptions concerning punishment severity and punishment certainty. 17 Therefore, hospital staff who attend these SETA programs are expected to possess a deeper knowledge about punishments of non-compliance to the ISP in addition to regular security policies and procedures.…”
Section: Theoretical Foundation Research Model and Hypothesesmentioning
confidence: 93%
“…16 In other words, proper compelling policies are required for useful security policy implementations. 49 Organizations should therefore make potential perpetrators aware of those enforcement rules in advance. 61 In this vein, if hospital staff are aware of the probability they will be punished when they are caught violating ISP, they will be more likely than not abide by the stated ISP.…”
Section: Theoretical Foundation Research Model and Hypothesesmentioning
confidence: 99%
“…Partially supported in 9 studies:  Computer abuse/crime (Dhillon et al, 2004;Harrington, 1996;Lee et al, 2004;Nicho & Kamoun, 2014;. Fan & Zhang, 2011;Hovav & D'Arcy, 2012) Not supported in 1 study:  Illegal policy violation (Hu, Xu, Dinev, & Ling, 2011) Noncriminal Supported in 18 studies:  Policy violation (Alshare et al, 2018;Barlow et al, 2013;Herath et al, 2018;Johnston et al, 2016;Khan & AlShare, 2019;Workman & Gathegi, 2007).…”
Section: About the Authorsmentioning
confidence: 99%
“…The extant literature on ISP compliance has mostly focused on employees’ attitudinal state (value), perceptions of punishment and reward and competency (skills) (Cram et al , 2019). According to Cram et al (2019), the following concepts showed a robust positive influence on employee’s ISP compliance: social values and beliefs (Bulgurcu et al , 2010; Guo et al , 2011; Cheng et al , 2013; D’Arcy and Greene, 2014), individual norms and morality (Myyry et al , 2009; Vance and Siponen, 2012; Ifinedo, 2014; Moody et al , 2018), a proper reward system (Bulgurcu et al , 2010; Chen et al , 2012), sanctions (Bulgurcu et al , 2010; Hu et al , 2012), self-efficacy (Bulgurcu et al , 2010; Burns et al , 2018) and SETA (Bulgurcu et al , 2010; Burns et al , 2018; Han et al , 2017; Herath et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%